2015
DOI: 10.1016/j.ijrobp.2015.07.2293
|View full text |Cite
|
Sign up to set email alerts
|

White and Gray Matter Abnormalities After Cranial Radiation in Children and Mice

Abstract: Changes in mice treated with cranial radiation are similar to those in humans, including significant WM and GM alterations. Because mice did not receive any other treatment, the similarity across species supports the expectation that radiation is causative and suggests mice provide a representative model for studying impaired brain development after cranial radiation and testing novel treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 52 publications
4
44
0
Order By: Relevance
“…Using the mouse, we have been able to describe the extent and localization of brain changes in response to pediatric whole‐brain irradiation (Gazdzinski et al., ), and define the most vulnerable periods in brain development (de Guzman et al., ). Importantly, we directly showed that our findings in these tightly controlled mouse studies relate closely to human brain imaging results (Nieman et al., ).…”
Section: Commentarysupporting
confidence: 78%
“…Using the mouse, we have been able to describe the extent and localization of brain changes in response to pediatric whole‐brain irradiation (Gazdzinski et al., ), and define the most vulnerable periods in brain development (de Guzman et al., ). Importantly, we directly showed that our findings in these tightly controlled mouse studies relate closely to human brain imaging results (Nieman et al., ).…”
Section: Commentarysupporting
confidence: 78%
“…Xiong et al (2013) detected lower FA in the temporal region in the post-RT-ED group than that of the pre-RT group. The possible explanation for this discrepancy may be that WM is more sensitive to RT in the early delayed period (Nieman, et al, 2015) and temporal injury may mainly occur in WM in this period. While GM become sensitive to RT and change gradually in the late delayed period.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the decreased cortical thickness in the PreCG in the post-RT-ED group may indicate RT-induced motor dysfunction, but the increased cortical thickness in the bSTS, LOC, ICC, and bilateral IPC in the post-RT-LD group may reflect that these regions compensate the impaired functions in the early stage to a certain extent. Actually, the increase of cortical thickness measured with MRI is affected by several factors in the cellular level, such as inflammation and gliosis (Nieman, et al, 2015) or central compensation after particular brain nerve deficits over time (zu Eulenburg, et al, 2010). In addition, it is important to emphasize that the interpretations directly relating macroscopic differences in cortical thickness measured with MRI to differences on the cellular level should be taken with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistence, on one aspect, could be related with diverse histological constitution in the brain between mice and humans. Specifically, the volume ratio of grey matter in the whole brain is notably higher in mice than in humans [30], and thus mice brains have more neurons to consume in the degenerative process. On another aspect, due to a long asymptomatic period, patients consenting to PET examination may be already at late-stage AD.…”
Section: Discussionmentioning
confidence: 99%